Comparative Effectiveness and Safety of Direct Oral Anticoagulants in Low Body Weight Patients with Atrial Fibrillation: A Systematic Review and Meta-analysis - Mohamed Nabil Elshafei (9960500) (2024)
Introduction Direct oral anticoagulant (DOAC) agents are established as the anticoagulation strategy of choice for a variety of clinical risks. Despite this, uncertainty still exists with regard to their efficacy and safety for the prevention of stroke and systemic embolism in some patient populations; most notably those with low body weight (LBW) (<60 kg or body mass index [BMI] <18 kg/m2). Currently, there is a paucity of trial and non-trial data to support a prescriptive recommendation for their use in these patient cohorts. We have carried out a pooled systematic review of the most up to date published data of patients stabilized on various DOAC analogs with the view to ascertaining the exact matrices of their efficacy and safety in these cohorts of patients. Methods We initially carried out a comprehensive search of databases from inception to June 2023 for eligible studies exploring the efficacy and safety of various analogs of direct oral anticoagulants in patients with atrial fibrillation who had low body weight. Databases accessed include PubMed, EMBASE, the Science Citation Index, the Cochrane Database of Systematic Reviews, and the Database of Abstracts of Reviews of Effectiveness. We carried out a weighted comparison of derived pooled odd ratios (with their corresponding confidence intervals) of mortality outcomes between various DOACs using the random effects model. Results Thirteen studies (n = 165,205 patients) were included in our meta-analysis. DOAC analogs were associated with increased stroke-related events, composite outcome, and mortality in low body weight patients compared to non-low body weight patients (odds ratio [OR] 1.50, 95% confidence interval [CI] 1.17–1.92), (OR 1.55, 95% CI 1.29–1.86), (OR 2.92, 95% CI 1.87–4.58), respectively. There was no significant difference in the safety outcome (major bleeding events) between the DOAC analogs (OR 1.19, 95% CI 0.93–1.52). Discussion In this meta-analytical review comprising both real-world and randomized controlled studies, the use of DOAC analogs in low body weight patients (body weight of <60 kg or BMI<18 kg/m2) with atrial fibrillation was associated with increased risks of stroke-related events, composite outcomes, and mortality compared to non-low body weight cohorts patients. At the same time, there was no significant difference in terms of major bleeding events. This finding has provided the first resolution of pervading uncertainty surrounding the use of DOAC analogs in these patient cohorts and suggests the need for follow-up confirmatory systematic studies in this group of patients. Other Information Published in: Cardiovascular Drugs and Therapy License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s10557-023-07537-x Additional institutions affiliated with: The View Hospital